2023
DOI: 10.3390/catal13030609
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Metal Nanoparticles on the Efficiency of Heavy Oil Aquathermolysis

Abstract: In this study, for the first time we investigated the in situ upgrading performance of Na metal nanoparticles, which were obtained by dispersing small pieces of sodium in liquid paraffin up to certain dispersity. In situ aquathermolytic reactions were modeled in a high pressure–high temperature reactor coupled with a Gas Chromatography (GC) system at a temperature of 250 °C for 24 h using a heavy oil sample, produced from the Ashal’cha reservoir, Republic of Tatarstan (Russia). The mean particle size of Na nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The cost of a nanofluid depends, fundamentally, on the cost of the synthesis precursors. , Davoodi et al presented a detailed discussion on the average cost in USD/g of some nanoparticles suitable for drilling fluid additives. For instance, SiO 2 , ZrO 2 , and Fe 2 O 3 are the cheapest nanoparticles with a value lower than 1 USD/g.…”
Section: Economic Potential Assessment Of a Nano-sagd Methodsmentioning
confidence: 99%
“…The cost of a nanofluid depends, fundamentally, on the cost of the synthesis precursors. , Davoodi et al presented a detailed discussion on the average cost in USD/g of some nanoparticles suitable for drilling fluid additives. For instance, SiO 2 , ZrO 2 , and Fe 2 O 3 are the cheapest nanoparticles with a value lower than 1 USD/g.…”
Section: Economic Potential Assessment Of a Nano-sagd Methodsmentioning
confidence: 99%
“…In our previous research, we demonstrated the high efficiency of nanodispersed metallic sodium, an easily obtainable material derived from simple dispersion . This led to the refinement and viscosity reduction of oil along with hydrogen sulfide neutralization.…”
Section: Introductionmentioning
confidence: 99%
“…39 In our previous research, we demonstrated the high efficiency of nanodispersed metallic sodium, an easily obtainable material derived from simple dispersion. 34 This led to the refinement and viscosity reduction of oil along with hydrogen sulfide neutralization. The objective of this study is to investigate the impact of the duration of the thermobaric process of TST in the presence of nanodispersed metallic sodium on the properties of the oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation